Holidays with my horse: Human-horse relationships and multispecies tourism experiences. (April 2020) - Dashper, Katherine
Abstract: More people are choosing to include their 'pets' and companion animals in their holidays, but provision for and understanding of nonhuman travellers remain limited. Multispecies tourism provides opportunity for the creation of rich, personally meaningful experiences that are key to satisfaction, but also has potential for producing stress and disappointment. The limited field of multispecies tourism tends to focus on dogs, whereas this paper considers some of the different issues raised when humans and horses holiday together. Auto/ethnographic vignettes of human-horse partnerships 'on holiday' are used to consider questions of interspecies trust and relationships as enacted through tourism, and to reflect on some of the complexities and contradictions inherent in these practices. These tourism activities prompt consideration of what makes a 'good' holiday and for whom, as well as some of the power relations inherent in multispecies tourism. Highlights: More people are choosing to holiday with pets and companion animals. Understanding about multispecies tourism is limited. Multispecies holidays are built on emotion and embodied interspecies relationships. Multispecies holidays can stimulate debate about power relations in tourism.